Possibilities of Translating Specialized Language: An Analysis of the Translation of the Book “Das geheime Leben der Bäume” – "Tajni život drveća" - Zarifović Grković, Mirjana J.; Pajić Kopilović, Ivana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This study examines the Serbian translation of Peter Wohlleben’s The Hidden Life of Trees into Serbian (Tajni život drveća, 2017). Originally published in 2015 as Das geheime Leben der Bäume, the book blends popular science with specialized forestry terminology, creating both linguistic and methodological challenges for translation. The main objective of this research is to systematically analyse the translation strategies and techniques used to render domain-specific terminology into Serbian. Framed within contrastive linguistics and translation studies, the study adopts an integrative methodological approach that combines descriptive and contrastive analyses. The corpus comprises 171 lexemes identified in both the German original and the Serbian translation. Through the examination of selected examples, the study evaluates the appropriateness and consistency of the applied strategies. The analysis reveals that the translator encountered various linguistic and terminological difficulties. Although Serbian equivalents exist for many German technical terms—often as internationalisms, calques, or established lexical units—their use is not always straightforward, complicating direct equivalence. Consequently, a range of translation techniques was employed to preserve both terminological accuracy and textual clarity. Following Chesterman’s typology, these strategies are grouped into three categories: syntactic (cohesion change, level shift, clause structure change, unit shift), semantic (emphasis change, hyponymy, abstraction change, distribution change), and pragmatic (explicitness change, interpersonal change, visibility change, coherence change). In addition, procedures such as concretization and paraphrasing, as described by Hlebec, were also applied. The findings indicate that the translator frequently resorted to specific techniques, demonstrating considerable professional competence and methodological sensitivity. At the same time, certain choices appear debatable, underscoring the complexity of specialized translation. Despite these terminological challenges, the translation largely fulfills its purpose: the text reads fluently and remains accessible, requiring only occasional clarifications. The Serbian version thus contributes to disseminating specialized knowledge to a broader audience and serves as a valuable case study of typical challenges and solutions in technical translation.